A quick method to investigate the Drosophila Johnston's organ by confocal microscopy. Issue 1 (March 2015) - Mishra, Monalisa
Abstract: Drosophila antennae is gaining attention to study the hearing molecules and its mechanism in last few decades. Various molecules required for the formation of hearing organ is conserved between Drosophila and human being. This suggests Drosophila can be used as a model organism to decipher the vertebrate hearing mechanism. In this context a protocol describing the fixation, sectioning and staining of antennae is lacking from the literature. The current paper describes various commercially available markers of the antennae to visualise it under confocal microscope.